2014
DOI: 10.1016/j.cub.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Is a Versatile and Long-Lived Chaperone for Desiccation Tolerance

Abstract: Our results suggest that trehalose is both a more stable and more versatile protectant than protein chaperones, explaining its important role in desiccation tolerance and emphasizing the translational potential of small chemical chaperones as stress effectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
210
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(221 citation statements)
references
References 38 publications
10
210
1
Order By: Relevance
“…With respect to desiccation, we found that trehalose has no protective effect when wild type cells are subjected to this stress. This is in line with results from Calahan et al (53) showing that mutants defective in trehalose biosynthesis retained wild type levels of desiccation tolerance, whereas a more recent report from the same group (54) proposed that trehalose is only needed for survival during long term (Ͼ2 days) desiccation. Our results also agreed with a previous work of Ratnakumar and Tunnacliffe (52) that pointed out a lack of correlation between trehalose levels and survival of the yeast S. cerevisiae during short-term desiccation.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to desiccation, we found that trehalose has no protective effect when wild type cells are subjected to this stress. This is in line with results from Calahan et al (53) showing that mutants defective in trehalose biosynthesis retained wild type levels of desiccation tolerance, whereas a more recent report from the same group (54) proposed that trehalose is only needed for survival during long term (Ͼ2 days) desiccation. Our results also agreed with a previous work of Ratnakumar and Tunnacliffe (52) that pointed out a lack of correlation between trehalose levels and survival of the yeast S. cerevisiae during short-term desiccation.…”
Section: Discussionsupporting
confidence: 90%
“…Trehalose is abundant in many, but not all, organisms that survive anhydrobiosis, an ametabolic state incurred by desiccation, oxidation, freezing, and heat, and all survived by Artemia during diapause and quiescence (Crowe et al 1992;Singer and Lindquist 1998a, b;Tunnacliffe et al 2005;Ratnakumar and Tunnacliffe 2006;Hengherr et al 2008;Erkut et al 2011Erkut et al , 2013Morano 2014;Tapia and Koshland 2014). Trehalose preserves membranes by blocking fusion, thus averting leakiness, and by lowering transition temperature (T m ), the latter proposed to come about by different but overlapping processes as follows (Crowe et al 1987(Crowe et al , 1992Clegg and Trotman 2002;Crowe 2007;Erkut et al 2011;Hengherr et al 2011).…”
Section: Trehalose and Stress Tolerance In Artemia Cystsmentioning
confidence: 99%
“…Stabilization favors protein renaturation by Hsp104 which, with trehalose, is strongly induced in moderately stressed and stationary-phase yeast. Hsp104, an energyrequiring molecular chaperone, promotes short-term dehydration tolerance in yeast (Tapia and Koshland 2014). Conversely, trehalose maintains both short-and long-term protein homeostasis by an energy-independent mechanism effective even when organisms experience metabolic depression, desiccation, and ATP limitation, as occur in Artemia cysts during diapause and quiescence (Crowe et al 1987;Tapia and Koshland 2014).…”
Section: Trehalose and Stress Tolerance In Artemia Cystsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in saturated cultures, yeast cells accumulate high levels of a number of stress effectors, including extremely high levels of trehalose (up to 15% of dry cell mass) (6,7). We recently showed that high levels of trehalose are necessary for yeast cells in saturated cultures to survive weeks to months of desiccation (long term), but not a few days (short term) (9). Trehalose dispensability during short-term desiccation is due in part to overlapping functions with the heat shock factor Hsp104.…”
mentioning
confidence: 99%